Determinants of Increased Customer Loyalty at PT Logistik Indonesia Network Thru Customer Satisfaction as an Intervening Variable - Widarma; Sufrin Hannan; Agus Setyo Pranowo (International Journal of Economics Accounting and Management, 2026)
This study aims to examine the influence of service quality and price perception on customer loyalty, with customer satisfaction as an intervening variable. This research is expected to increase customer loyalty at PT Logistik Indonsia Network. The sampling method used Purpossive and Simple Random Sampling by distributing questionnaires to 173 B2B respondents of PT Logistik Indonesia Network. The questionnaire data was processed using SMART PLS software version 4.0.9.9. The research results indicate that service quality and price perception have a positive and significant impact on customer satisfaction. Service quality has a positive but insignificant impact on customer loyalty, while price perception has a positive and significant impact on customer loyalty. Customer satisfaction is able to mediate between service quality and price perception toward customer loyalty. This finding confirms that in the B2B logistics industry, customer loyalty enhancement strategies are not sufficient by simply improving service quality, but must also be balanced with competitive pricing and the creation of satisfying customer experiences. PT Logistik Indonesia Network can consider optimizing service effectiveness, improving delivery timeliness, and developing more flexible pricing schemes to enhance customer satisfaction and loyalty.